2017
DOI: 10.1111/jiec.12583
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Carbon Dioxide–Based Production of Methane and Methanol and Derived Polymers

Abstract: Summary Previous studies showed that using carbon dioxide (CO2) as a raw material for chemical syntheses may provide an opportunity for achieving greenhouse gas (GHG) savings and a low‐carbon economy. Nevertheless, it is not clear whether carbon capture and utilization benefits the environment in terms of resource efficiency. We analyzed the production of methane, methanol, and synthesis gas as basic chemicals and derived polyoxymethylene, polyethylene, and polypropylene as polymers by calculating the output‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 52 publications
1
74
1
2
Order By: Relevance
“…Biopolymers can be defined as polymers that are not "harmful" for the environment. The concept of a biopolymer is strongly linked to the origin of the material (petrochemical or natural resource) and to its end-of-life (whether it is biodegradable or not) [1][2][3][4]. Biopolymers include petroleum-derived polymers with the biodegradation (disintegration in controlled compost soil conditions) feature.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymers can be defined as polymers that are not "harmful" for the environment. The concept of a biopolymer is strongly linked to the origin of the material (petrochemical or natural resource) and to its end-of-life (whether it is biodegradable or not) [1][2][3][4]. Biopolymers include petroleum-derived polymers with the biodegradation (disintegration in controlled compost soil conditions) feature.…”
Section: Introductionmentioning
confidence: 99%
“…Possible compression steps are environmentally relevant as they are associated with increased electricity demand. Other studies have shown that CO 2 ‐based polymer production saves greenhouse gas emissions, but is associated with increased raw material costs .…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature covering the environmental benefit of CO 2 polymerisation with epoxides to produce polycarbonates, thereby achieving carbon capture and utilisation (CCU), and contributing towards a mitigation of climate change . However, it is important that newly designed industrial processes to mitigate greenhouse gas emissions do not introduce new hazards .…”
Section: Introductionmentioning
confidence: 99%